2010
DOI: 10.1016/j.brainres.2010.03.063
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide gene expression analysis identifies K-ras as a regulator of alcohol intake

Abstract: Adaptations in the anterior cingulate cortex (ACC) have been implicated in alcohol and drug addiction. To identify genes that may contribute to excessive drinking, here we performed microarray analyses in laser microdissected rat ACC after a single or repeated administration of an intoxicating dose of alcohol (3g/kg). Expression of the small G protein K-ras was reduced following both single and repeated alcohol administration. We also observed that voluntary alcohol intake in K-ras heterozygous null mice (K-ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 70 publications
3
22
0
3
Order By: Relevance
“…Heterozygous Nf1 (+/−) and homozygous K-Ras (−/−) mice do not escalate ethanol consumption after CIE (Repunte-Canonigo et al, 2015; Repunte-Canonigo et al, 2010), similar to what we observed in Alk −/− mice. Neurofibromin is a Ras GTPase activating protein and a negative regulator of Ras/ERK signaling.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Heterozygous Nf1 (+/−) and homozygous K-Ras (−/−) mice do not escalate ethanol consumption after CIE (Repunte-Canonigo et al, 2015; Repunte-Canonigo et al, 2010), similar to what we observed in Alk −/− mice. Neurofibromin is a Ras GTPase activating protein and a negative regulator of Ras/ERK signaling.…”
Section: Discussionsupporting
confidence: 88%
“…CIE has been shown to increase GABA neurotransmission in rats and mice (Repunte-Canonigo et al, 2015; Repunte-Canonigo et al, 2010; Roberto et al, 2004). Although ethanol-naïve Alk −/− mice display increased GABA release, GABA neurotransmission after CIE is not augmented in Alk −/− mice as it is in Alk +/+ mice.…”
Section: Discussionmentioning
confidence: 99%
“…Rats with a history of excessive alcohol intake and abstinence show activation of HRAS in the NAc 25 , and downregulation of HRAS expression or inhibition of its activity in the NAc attenuates the self-administration of alcohol in models of excessive alcohol intake in mice (20%IA2BC paradigm) and rats (20%IA2BC and 20%LA models)25. In line with these findings, escalation of alcohol drinking (20%LA procedure) is not detected in mice with heterozygous knockout of the gene encoding another member of the RAS GTPases, KRAS 43 .…”
Section: Go Pathways Promote Excessive Drinkingsupporting
confidence: 61%
“…1 and Table 3). The GTPase H-ras encoded by HRAS in the nucleus accumbens plays a key role in neuroadaptations that underlie excessive alcohol-drinking behaviors in mice (Ben Hamida et al, 2012), while the GTPase K-ras encoded by KRAS is differentially expressed after repeated alcohol in the anterior cingulate cortex and alcohol differentially affected various pathways in a K-ras dependent manner suggesting that K-ras-regulatory pathways play a key role in excessive alcohol drinking after a history of dependence (Repunte-Canonigo et al, 2010). Thus genetic variation affecting the regulation of RASL11A could likely play a role in behaviors associated with protracted abstinence from alcohol and thus represents a novel and compelling candidate gene based on human GWAS and molecular biology studies in rodents.…”
Section: Genome-wide Association Studies Of Alcohol Dependencementioning
confidence: 99%